Strategi Pengembangan Usaha Budi Daya Ikan Nila (Oreochromis Niloticus) di Desa Sedari Kecamatan Cibuaya Kabupaten Karawang - Nugroho, Kent Farrel Ryan (Jurnal Ilmiah Wahana Pendidikan, 2024)
Tilapia (Oreochromis niloticus) is one of the leading commodities in the aquaculture sector. Nila Salin Village in Sedari Village, Cibuaya District, Karawang Regency is an area is a center for saline tilapia. There are several problems such as low quality of human resources, mastery of technology and marketing results. The purpose of this study to identify and analyze factors (strengths, weaknesses, opportunities and threats), analyze alternative strategies, and determine priorities of saline tilapia business strategies. Data in this study were obtained by quantitative methods, primary and secondary data were obtained by observation, interviews, and literature. Data analyzed using IFAS, EFAS, SWOT analysis, and Grand Strategy matrices. Based on the data processed and analyzed, total IFAS score is 3,257 and total EFAS score is 3,289. In SWOT matrix, alternative strategies were obtained, namely SO, ST strategy, WO strategy and WT strategy, and the development of tilapia farming business (Oreochromis niloticus) in Sedari Village located in quadrant 1 with coordinate points (0.779, 0.786). IFAS and EFAS analysis shows that the development of tilapia business (Oreochromis niloticus) in Sedari Village is to take advantage of opportunities, through SWOT matrix, eight alternatives were obtained which used as development of saline tilapia business.